Light-Emitting Diodes: Research, Manufacturing, and Applications XI 2007
DOI: 10.1117/12.701344
|View full text |Cite
|
Sign up to set email alerts
|

Employing a 2D surface grating to improve light out coupling of a substrate emitting organic LED

Abstract: We present simulation and experimental results to achieve increased light extraction of a substrate emitting OLED. We present a comparison between a grating surface on the OLED and an array of microlenses at the interface between substrate and air. This experimentally gives -in both cases-a relative improvement of approx. 30 %. We also demonstrate the concept of a RC 2 LED, applied to an OLED. The RC 2 LED is composed by adding a high, low and high index layers between ITO and glass, i.e. the interface between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…From the simulation results, it was found that the surface PhCs play a poor role in enhancing the out-coupling efficiency of the OLEDs (about 120%). In the experiment, the enhancement factor F of about 130% with surface PhCs was obtained [21].…”
Section: Influence Of the Embedded Phcs On The Enhancement Of The Outmentioning
confidence: 92%
“…From the simulation results, it was found that the surface PhCs play a poor role in enhancing the out-coupling efficiency of the OLEDs (about 120%). In the experiment, the enhancement factor F of about 130% with surface PhCs was obtained [21].…”
Section: Influence Of the Embedded Phcs On The Enhancement Of The Outmentioning
confidence: 92%
“…It should be noted that with these refractive indexes, the critical angle for total reflection is 40 • , as given by (8), so that none of the incidence angles θ i between 40 • and 90 • contribute to the transmission. At small angles, for θ i near 0 • , the geometric factor sin θ i also cuts the transmission efficiency, even if the Fresnel's transmission coefficient is strong there (about 95%).…”
Section: Light Extraction From An Homogeneous Medium Terminated By a mentioning
confidence: 99%
“…When a source emits from inside a high refractive index medium, the emitted light that reaches the surface will not always be able to escape into the air, because of the total reflection at large incidence angles. The external efficiency of all electroluminescent devices made from semiconductors [7] is affected by this effect, and this is especially true for the recently developed large-size organic light-emitting diodes [8,9]. The firefly lantern is no exception and it is interesting to parallel the decades of semiconductor diodes structural optimized engineering with some hundred million years of blind natural selection in these living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This result may seem surprisingly low, especially for a medium with a very moderate refractive index, such as the one considered here. It should be noted that with these refractive indexes, the critical angle for total reflection is 40 • , as given by (8), so that none of the incidence angles θ i between 40 • and 90 • contribute to the transmission. At small angles, for θ i near 0 • , the geometric factor sin θ i also cuts the transmission efficiency, even if the Fresnel's transmission coefficient is strong there (about 95%).…”
Section: Light Extraction From An Homogeneous Medium Terminated By a ...mentioning
confidence: 99%
“…When a source emits from inside a high refractive index medium, the emitted light that reaches the surface will not always be able to escape into the air, because of the total reflection at large incidence angles. The external efficiency of all electroluminescent devices made from semiconductors [7] is affected by this effect, and this is especially true for the recently developed large-size organic light-emitting diodes [8,9]. The firefly lantern is no exception and it is interesting to parallel the decades of semi-conductor diodes structural optimized engineering with some hundred million years of blind natural selection in these living organisms.…”
Section: Introductionmentioning
confidence: 99%